ESTUDO PSICOFARMACOLÓGICO DO EXTRATO BRUTO DAS CASCAS DE Himatanthus drasticus MART - Pinto, Bruno Araújo Serra (2011)
Himatanthus drasticus Mart. popularly known as janauba, is so widely used medicinally as antitumor, antiulcer and analgesic. Pharmacological studies carried out previously found antiulcerogenic, anti-inflammatory, analgesic and antitumor actions of crude extract and isolated compounds of the species. This study investigated psychopharmacologicals effects of acute administration of hydroalcoholic extract (EHA) from the barks of Himatanthus drasticus in mice. Initially, we performed a pharmacological behavioral screening to investigate potential changes induced by EHA. Swiss male mice were treated with EHA (10, 30 and 100 mg/kg) or vehicle (0.9% saline) 30 min (ip) before experiments. Were observed sedative and neuroleptic effects of the extract in a dose dependent. The EHA showed low toxicity with DL50 of 3.4 g/kg. Because of the potent sedative effect appears even at low doses, the study was directed to perform tests related to a central nervous system depressant, such as hypnosedated, anticonvulsant and neuroleptic tests. To this end, potentiation of barbiturate-induced sleep, induction of catalepsy and induction of seizures with pentilenoteteazol (PTZ) and strychnine (STR) were chosen. Significant effects were observed potentiation of hypnosis and state of catatonia with all doses of EHA gradually. There were no decreases in seizure parameters of the treated animals in testing for strychnine convulsions, thus excluding the involvement of glycine mechanisms mimetics. In the test of PTZ-induced seizures, the EHA showed a significant anticonvulsant activity and bioprotector in all parameters evaluated and at all doses tested in a manner very similar to the positive control (diazepam), suggesting an involvement of the EHA-level gabaergics receptors, explaining satisfactorily the sedative and anticonvulsant presented. With that, this test was chosen to evaluate the alkaloids total fraction (FAT) at doses of 3 and 10 mg/kg, but the FAT did not have results significant as the EHA, suggesting that the effects of the extract are related to other secondary metabolites or fitocomplex. Our results demonstrate for the first time, anticonvulsant, neuroleptic and hypnosedated actions of H. drasticus extact, guiding future work aimed at elucidating the mechanisms by which these effects are mediated.